Leveraging GIS mapping and smart metering for improved OMS and SAIDI for smart city - Pathak, Sandeep (2016 Saudi Arabia Smart Grid (SASG), 2016)
State Governments across the globe have an ambitious plan to transform the existing and new cities into "SMART CITY" with very objective to make cities "Livable", "Reliable", "Safe", and "Comfortable" for citizens. Smart Grid is an inherent and integral part of the Smart City Program. Smart Grid in Smart City ensures Reliable, Safe and Quality Power 24/7 to its citizens at reasonable rates. However Distribution Grids are subject to frequent failure that can cause planned and unplanned power interruptions for utility customers. Major faults and outages on power distribution system have a significant economic and social impact. Despite advances by utility industry to protect and harden electrical grid, unplanned outages and faults critically jeopardize the "Availability" & "Reliability" of power supply. Therefore Power Distribution Utilities are challenged to improve their SAIDI for end customer satisfaction to commensurate with Smart City Standards. The SAIDI, (System Average Interruption Duration Index) is the average outage duration for each customer served, includes both planned and unplanned minutes off supply. Over last decade there has been significant improvement by power utilities worldwide in deploying Smart Grid solutions like GIS, AMI, SCADA-DMS, FPI, Customer Care, IVRand ERP to improve the operational efficiency of the utility. This paper describes that how business processes like AMI, GIS, CIS, FPI and SCADA-DMS help in improving the performance of Outage Management System (OMS) to efficiently manage the outage and thereby addressing both technical and organizational issues faced by the distribution utilities in the event of outages. These not only improve the utility performance, to be measured in terms of SAIDI, but also significantly improve the customer satisfaction and the attitude to wads utility and really makes city Smart.